Gender difference in extreme cardiac remodelling in endurance olympic athletes assessed by non-contrast CMR. (8th February 2021) - Maestrini, V; Birtolo, LI; Filomena, D; Di Giacinto, B; Squeo, MR; Mango, R; Di Gioia, G; Lemme, E; Serdoz, A; Fallanca, A; Severino, P; Gualdi, G; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Male and female athletes present difference spectrum of cardiac remodelling related to their sport activity. However data in elite female athletes are scarce and mainly limited to echocardiography evaluation. Purpose: The aim of the study was to assess gender difference in extreme cardiac remodelling in Olympic athletes engaged in endurance sport assessed by non-contrast Cardiovascular Magnetic Resonance including Mapping. Methods Olympic athletes engaged in endurance sport (rowing, canoeing, mid/long distance swimming) were examined with history, physical examination, 12-lead and exercise electrocardiogram, and echocardiography as part of their evaluation prior the Olympic games (Tokyo 2020). Athletes with unremarkable evaluation were undergone to non-contrast CMR including Mapping. The following parameters were calculated: indexed left ventricle (LV) and right ventricle (RV) end-diastolic (EDVi) and end-systolic volumes (ESVi), stroke volume (SVi), ejection fraction (EF), left and right atria area (LAAi and RAAi), LV Mass (Massi) and maximum wall thickness (MWT), RV/LV EDV ratio, spericity index [SI=(long axis diameter/2)3 * 4, 187], myocardial native T1 (nT1) and T2 Mapping. Results: 51 caucasian elite athletes (without difference in term of age, years of training and hours of training/week) were enrolled and 59% were male. Male showed greater LV EDVi (123 ± 28 ml vs 103 ± 10, p = 0.003), ESVi (55 ± 14 ml vs 44 ± 7, p = 0.001), SVi (68 ± 15 ml vs 59 ± 7, p = 0.023), Massi (76 ± 19 vs 57 ± 10, p < 0.001), MWT (10 ± 1 mm vs 8 ± 1, p < 0.001) and RV EDVi (129 ± 48 ml vs 104 ± 13, p = 0.026), ESVi (57 ± 10 ml vs 45 ± 9, p < 0.001), SVi (68 ± 15 ml vs 59 ± 7, p = 0.018) compared to female, as expected. LVEF (p = 0.05) and RVEF (p = 0.17) did not show significant difference. Despite greater volumes, SI (43 ± 12% vs 44 ± 8, p = 0.8) and RV/LV EDV ratio (0.99 ± 0.05 vs 1 ± 0.05, p = 0.405) did not differ between male and female athletes, as well as LAAi (13 ± 3 cm2 vs 13 ± 1.5, p = 0.86) and RAAi (13 ± 1.9 vs 13 ± 18, p = 0.56). Native T1 mapping was lower in male compared with female (934 ± 21 ms vs 956 ± 33, p = 0.028) while T2 Map values were slightly higher (53 ± 3.9 ms vs 50 ± 3.8, p = 0.027) . Conclusions: Male endurance Olympic athletes presented higher volumes and LV mass compared to their female counterparts, while atria dimension, systolic function and sphericity index did not differ. Ventricles showed balanced dilatation in both gender. Lower T1 value observed in male suggested cellular hypertrophy. Figure 1 showed CMR images in a male (top row) and a female (bottom row) Olympic athletes: 4 chamber end-diastolic and end-systolic frame and end-diastolic basal short axis (SAX) showed balanced dilatation. Graphs showed higher EDVi and Massi in male compared o female, no difference in sphericity index and lower native T1 mapping.